Augmented Reality Based Spelling Assistance to Dysgraphia Students - Muhammad Faizan Khan; Muhammad Azhar Hussain; Kamran Ahsan; Muhammad Saeed; Adnan Nadeem; Syed Asim Ali; Nadeem Mahmood; Kashif Rizwan (Journal of Basic & Applied Sciences, 2017)
Dysgraphia, a learning disability associated with writing skills, hinders students to put their thought on paper and write correctly. Writing problems hit students most frequently that one third students become failed to acquire writing skill. Different IT based assistance solutions available for dysgraphia students but most of them are accommodations based or provides writing alternatives rather than developing writing skills of a dysgraphia student. Handwriting is an essential skill for academic life and developed handwriting skill helps student to protect their self-esteem and build student’s confidence to participate in other activities during class. Most of available writing assistance solutions do not provide interesting ways to acquire writing skills. To handle this problem, augmented reality (AR) based dysgraphia assistance solution has presented in this work. This study utilized AR to develop dysgraphia student’s interest in writing and used it to assist in writing activity by providing help in spellings. AR based dysgraphia assistance writing environment (AR-DAWE) modal use Google cloud API of speech-to-text and addressed one of the important issues of dysgraphia student that is associated with spelling mistakes.